STRENGTHENING CHARACTER EDUCATION PROGRAM IMPLEMENTATION AT 100703 BATANG TORU ELEMENTARY SCHOOL THROUGH 5S ACTIVITIES - Rahmadhani, Astary Desty; Sapri, Sapri (Pascasarjana Universitas Islam Negeri Raden Fatah Palembang, 2023)
Being friendly or communicative is a behavior that is done to show a sense of pleasure in talking, getting along, and cooperating with others. One of the methods that can be applied at school to support communicative character is the culture of smiling,greeting,saluting, politeness, and manners, an Eastern culture that must remain attached to the Indonesian nation. This study aimed to determine the program's implementation to strengthen student character education through 5S activities at100703 Batang Toru Elementary School. This research method uses qualitative research methods. Data collection techniques use observation and interviews, which are then analyzed using data reduction, data presentation, and conclusion. The results of this study show that 100703 Batang Toru Elementary Schoolimplements the 5S program through a self-development program that includes routine activities, spontaneous activities, exemplary activities, and conditioning implemented in subjects and extracurricular activities. This 5S program has been implemented since 2012. The results of this study also show that the benefits of the 5S implementation have shown positive results in creating students' communicative character in the school environment.